2011
DOI: 10.1159/000334089
|View full text |Cite
|
Sign up to set email alerts
|

Altered HLA Class I and HLA-G Expression Is Associated with IL-10 Expression in Patients with Cervical Cancer

Abstract: Although high-risk human papillomaviruses (HPVs) are an important risk factor in the etiopathogenesis of cervical cancer, increasing evidence suggests that the ability to avoid immune surveillance seems to be linked to the transforming potential of HPV and a rapid progression to cancer. In other cancer models, IL-10 contributes to impair anti-tumor immune response either by downregulating human leukocyte antigen Class I (HLA-I) expression or by increasing HLA-G expression. To comprehend how these alterations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 125 publications
(86 reference statements)
8
43
0
1
Order By: Relevance
“…In previous studies, HLA-G expression was found in 27–30 % of the primary- [28, 55] and 11 % of the metastatic tumor samples [28], but without histological subtyping. Here, comparable results were obtained with approximately 25 % of the cases having expression of HLA-G in the primary tumor and 11 % in the metastatic LNs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, HLA-G expression was found in 27–30 % of the primary- [28, 55] and 11 % of the metastatic tumor samples [28], but without histological subtyping. Here, comparable results were obtained with approximately 25 % of the cases having expression of HLA-G in the primary tumor and 11 % in the metastatic LNs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that HLA-G expression is negative in normal cervical tissues. Though no normal cervical tissues were included, Rodríguez et al [29] found that HLA-G protein expression (mAb 4H84) was observed in 27.6% (16/58) of cases. To the contrary, a study by Zhou et al [30] addressed that a strong and uniform HLA-G expression (mAb MEM-G/1) in normal epithelium, while only a small proportion of CINs and cervical squamous cell carcinoma samples showed reduced expression of HLA-G.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 contributes to the impairment of the anti-tumor immune response, either by downregulating human leukocyte antigen Class I expression or by increasing HLA-G expression in human trophoblasts and monocytes (46,47) and certain cancer models, such as lung cancer (48). HLA-G is known to inhibit the cytotoxic activity of T lymphocytes and natural killer (NK) cells (49,50), which is associated with cancer development and immune tolerance.…”
Section: Il-10 Exerts a Tumor-promoting Effect In Cervical Cancermentioning
confidence: 99%